1994
DOI: 10.2337/diacare.17.12.1428
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes With Mitochondrial Gene tRNALYS Mutation

Abstract: This observation is the first report of association of diabetes with the mitochondrial tRNA(LYS) mutation. Insulin secretory capacity was significantly lower in the mutant members than in the nonmutated members. These findings suggest that the pancreatic beta-cell secretory defect of insulin might be one of the phenotypes of the mitochondrial tRNA(LYS) mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…On the other hand, the latter tRNA Leu(UUR) 3243 mutation was prevalently found in peripheral leukocytes and muscle of more than 1% patients with diabetes mellitus (8), indicating that these mutations could contribute to the pathogenesis of the disease. More recently, several point mutations other than that at nucleotide position 3243 in the tRNA Leu(UUR) gene (42), and point mutations in the tRNA Lys gene at 8344 (43) and the tRNA Glu gene at 14,709 (44,45) were also observed in patients with diabetes mellitus. However, there is as yet no convincing evidence that the mitochondrial dysfunction induced by these mtDNA mutations is responsible for the pathogenesis of the disease, although it had already been shown that the accumulation of some of the mtDNA mutations in cultured somatic cell lines was sufficient to induce the mitochondrial dysfunction through inhibition of overall mitochondrial translation (16 -20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the latter tRNA Leu(UUR) 3243 mutation was prevalently found in peripheral leukocytes and muscle of more than 1% patients with diabetes mellitus (8), indicating that these mutations could contribute to the pathogenesis of the disease. More recently, several point mutations other than that at nucleotide position 3243 in the tRNA Leu(UUR) gene (42), and point mutations in the tRNA Lys gene at 8344 (43) and the tRNA Glu gene at 14,709 (44,45) were also observed in patients with diabetes mellitus. However, there is as yet no convincing evidence that the mitochondrial dysfunction induced by these mtDNA mutations is responsible for the pathogenesis of the disease, although it had already been shown that the accumulation of some of the mtDNA mutations in cultured somatic cell lines was sufficient to induce the mitochondrial dysfunction through inhibition of overall mitochondrial translation (16 -20).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the different results may be in the selection of patients, the difference in races, the use of different methods, and the degree of heteroplasmy. The degree of heteroplasmy reported differs in various tissues and in various subjects (15,16,26). Larsson et al (25) reported that Ͼ92% of mtDNA with the tRNA Lys 8344 mutation in muscle is needed to cause respiratory chain dysfunction detected by biochemical methods, and the levels of mutated mtDNA in lymphocytes were 12.0 to 27.6% of those in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Oka et al (20) reported that the tRNA Leu(UUR) 3243 mutation is missing in patients who were initially diagnosed with NIDDM and then progressed to insulin dependency within a few years. They speculated that the tRNA Leu(UUR) 3243 mutation may cause gradual ␤-cell destruction, but no direct correlation was found between the percentage of mutation in tRNA Lys 8344 in peripheral leukocyte and ␤-cell secretory function (16). Whereas Van den Ouweland et al (21) reported that insulin secretion was apparently normal in affected patients, suggesting the pathogenic importance of peripheral insulin resistance, Alcolado et al (22) and others (23,24) have shown that in the diabetes with mtDNA mutations, the sensing pathway may be intact, and the prevailing hyperglycemia results in increased concentrations of insulin precursors typical of those seen in patients with NIDDM and impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin secretory capacity was significantly lower in the mutant members than in the nonmutant members. 229 The tRNA Glu A14709G mutation which has been associated with maternally inherited diabetes and deafness, 116 has also been detected in a family in which mother and son were affected with diabetes mellitus and myopathy without hearing loss. 168 Neurodegenerative disorders.…”
Section: The Clinical Phenotypes Of Mitochondrial Trna Mutationsmentioning
confidence: 99%